Pengelolaan Tanah Ulayat dalam Masyarakat Minangkabau Kontemporer: Studi Kasus Masyarakat Nagari Sungai Kamuyang - Syaputra, Fendi Agus; Afrizal, Afrizal (Jurnal Sosiologi Andalas, 2025)
The transition from communal to individual land ownership in modern society, as posited by replacement theory, has profound implications for land management practices. This study critically examines the practices surrounding customary land (tanah ulayat) within the Minangkabau community, specifically in Nagari Sungai Kamuyang, West Sumatra, thereby challenging prevailing theoretical assumptions. Utilizing a qualitative approach, the research incorporates in-depth interviews and field observations to understand the community's strategies for managing and utilizing customary land. Findings reveal that the Nagari Sungai Kamuyang community actively upholds the ulayat land status as a collective right and effectively administers it to promote the welfare of its members. The management of customary land occurs under the guidance of traditional leaders (niniak mamak) and local government authorities, with regulations that permit usage rights without transferring ownership. This collective stewardship not only sustains livelihoods for community members, particularly those lacking access to agricultural land, but also reinforces the social values intrinsic to ulayat land. These practices demonstrate the community's resilience and offer a robust counterargument to the predictions of replacement theory.